Hubungan Kecerdasan Emosional Dan Umur Mahasiswi Semester I DIV Kebidanan Tahun 2017 - Triwik Sri Mulati (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract: Emotional Intelligence, Age, First Semester Students Of Div Midwifery Programme. The aim of this research was to know the descriptive of the type and the level of perineum laceration on post partum mother at Klaten. This research was descriptive design. The data were analyzed using descriptive statistics. The respondents were 48 students who are the first semester students of DIV Mdwifery Programme at Poltekkes Kemenkes Surakarta. The results of this study indicate p = 0359, where p>0.05, so it can be concluded that there is no relationship between emotional intelligence and age on the students DIV DIV Midwifery Programme at Poltekkes Kemenkes Surakarta.